Pemanfaatan Teknologi Artificial Intelligence (Ai) Dalam Penilaian Ketrampilan Membaca Teks Berbahasa Arab - Moh Zainal Abidin Aris; M Yunus Abu Bakar (Journal of Innovative and Creativity, 2025)
Assessing reading skills in Arabic language learning is a crucial aspect that demands effective, objective, and adaptive approaches to student needs. However, in practice, traditional assessments often face constraints such as time limitations, teacher subjectivity, and a lack of evaluation tools capable of comprehensively measuring student comprehension. This paper aims to explore the utilization of AI technology, specifically AI Form Grader and Reverso applications, as innovative assessment solutions for evaluating reading skills in Arabic texts. AI Form Grader facilitates automatic correction of multiple-choice and short-answer questions related to reading comprehension, while Reverso is used to analyze sentence structure, contextual translations, and the accuracy level of students' comprehension of Arabic texts. Through a literature review approach and descriptive analysis, this paper presents a study on the advantages, challenges, and integration strategies of these two tools in technology-based Arabic language learning. The results indicate that the implementation of AI can enhance the efficiency, accuracy, and objectivity of assessment, while also encouraging students to be more independent and reflective in understanding Arabic texts. Thus, the utilization of AI technology in this context can be a significant breakthrough in the development of innovative assessment systems in Arabic language learning.